Are Extracorporeal Shock Waves Just a Therapeutic Tool? - Bernardo Gialanella; Laura Comini; Gian Pietro Bonometti; Fabio Vanoglio; Andrea Bettinsoli; Raffaele Santoro; Adriana Olivares; Alberto Luisa (Diagnostics)
Background: Focused extracorporeal shock wave therapy (ESWT) has been successfully used to treat musculoskeletal conditions, but ESWT stimulates nociceptors, causing pain deep in the tissue during treatment. The occurrence of pain during ESWT is a side effect, but it can help identify painful sites and assess minimum (MiTI) and maximum (MaTI) pain thresholds to ESWT pressure stimuli. This topic has received limited attention in literature. Methods: This observational study describes a specific approach to using ESWT to study pain in 71 patients. The approach proposes moving the ESWT transducer head of the device over the entire joint surface, progressively increasing the energy level until the patient experiences pain. Results: In the study, MiTI and MaTI were 0.218 ± 0.090 and 0.416 ± 0.165 mJ/mm2 in the affected joint and 0.282 ± 0.128 and 0.501 ± 0.174 mJ/mm2 in the contralateral homologous healthy joint, being significantly lower in the affected joint (MiTI: p < 0.001 and MaTI: p = 0.003, respectively). ESWT induced pain in 94.37% of the sites with the highest subjective pain and in a greater number of sites (204) than digital pressure (123) (p < 0.001). All sites with digital pressure pain also had ESWT pain. Conclusions: These results suggest that the ESWT device may be useful in investigating pain in musculoskeletal conditions and tailoring therapy.